Association of allostatic load with all‐cause and cause‐specific dementia: A prospective cohort study - Yifan Gou; Xin Qi; Chen Liu; Jingni Hui; Ye Liu; Meijuan Kang; Ruixue Zhou; Bingyi Wang; Panxing Shi; Feng Zhang (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract INTRODUCTION Allostatic load (AL) serves as a valuable tool for objectively assessing the biological impact of chronic stress and has been implicated in dementia risk. This study aims to investigate the association between AL and all‐cause dementia, Alzheimer's disease (AD), vascular dementia (VaD), and non‐Alzheimer non‐vascular dementia (NAVD). METHODS This prospective study included 361,920 adults from the UK Biobank, with an observation period extending from March 13, 2006, to October 31, 2022, excluding participants with prior dementia diagnoses. AL was estimated through 10 biomarkers related to the dysregulation of metabolic, cardiovascular, and inflammatory systems. Diagnoses were based on the International Classification of Diseases, 10th Revision (ICD‐10). We performed Cox proportional hazards models to assess the relationship between AL and dementia. Additionally, we conducted subgroup analyses for sex, Townsend Deprivation Index (TDI), and smoking, along with sensitivity analyses. RESULTS The median follow‐up period was 12.88 years. Over the follow‐up period, 6155 (1.70%) participants developed all‐cause dementia, 2762 (0.76%) developed AD, 1316 (0.36%) developed VaD, and 3790 (1.05%) developed NAVD. In the fully adjusted model, high AL was associated with an increased risk of all‐cause dementia (hazard ratio [HR]: 1.269, 95% confidence interval [CI]: 1.159–1.390), VaD (HR: 1.934, 95% CI: 1.569–2.384), and NAVD (HR: 1.253, 95% CI: 1.116–1.408). Women and non‐smoking individuals with high AL were vulnerable to VaD, and the associations between AL and all‐cause dementia were stronger in people with high TDI. DISCUSSION AL is positively associated with an elevated risk of dementia, underscoring its effect as a risk factor in the neurodegenerative process that provokes dementia. Highlights This study estimated allostatic load (AL) index through 10 biomarkers. The associations between AL and all‐cause and cause‐specific dementia were evaluated. Elevated AL is a risk factor for all‐cause dementia and vascular dementia.